2023
DOI: 10.1007/s11160-023-09770-x
|View full text |Cite
|
Sign up to set email alerts
|

An approach to assess data-less small-scale fisheries: examples from Congo rivers

Abstract: Small-scale fisheries (SSF) account for much of the global fish catch, but data to assess them often do not exist, impeding assessments of their historical dynamics and status. Here, we propose an approach to assess 'data-less' SSF using local knowledge to produce data, life history theory to describe their historical multispecies dynamics, and length-based reference points to evaluate stock status. We demonstrate use of this approach in three data-less SSFs of the Congo Basin. Fishers' recalls of past fishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…In the Congo Basin study, regression models that were fitted to unfiltered recalls of typical harvests revealed declines in catch on the order of 65-80% during the past halfcentury. Findings from Castello et al (2023) in the Congo Basin demonstrate that, despite variability, samples of recalls can effectively produce historical resource-level information, and the results of the present study indicate that such information is almost as reliable as data collected from conventional fisheries monitoring.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the Congo Basin study, regression models that were fitted to unfiltered recalls of typical harvests revealed declines in catch on the order of 65-80% during the past halfcentury. Findings from Castello et al (2023) in the Congo Basin demonstrate that, despite variability, samples of recalls can effectively produce historical resource-level information, and the results of the present study indicate that such information is almost as reliable as data collected from conventional fisheries monitoring.…”
Section: Discussionmentioning
confidence: 51%
“…This was the case regardless of whether recalls were filtered to minimize age and time effects, most likely because such effects were generally small. The validity of these results is demonstrated by application of recalls of typical harvests to reconstruct catches in three "data-less" fisheries in the Congo Basin (Castello et al 2023), based on surveys of ~100 fishers per fishery. In the Congo Basin study, regression models that were fitted to unfiltered recalls of typical harvests revealed declines in catch on the order of 65-80% during the past halfcentury.…”
Section: Discussionmentioning
confidence: 95%
“…One small vein of this fastgrowing literature is of interest here, because it focuses on measuring spatial or temporal changes in the abundance or biomass of taxa or resources of conservation concern. Recent studies have surveyed local people asking them to estimate (qualitatively or quantitatively) the (relative or absolute) abundance or biomass of taxa or resources in different places or points in time (Van Holt, Townsend & Cronkleton, 2010;Gandiwa, 2012;Danielsen et al, 2014a;Danielsen et al, 2014b;Tomaselli et al, 2018;Naah & Braun, 2019;Henri et al, 2020;Afriyie & Asare, 2020;Benner, Nielsen & Lertzman, 2021;Djagoun et al, 2022;Castello et al, 2023). Some studies have analysed the raw data for trends (Tesfamichael, Pitcher & Pauly, 2014), while others have used advanced methods (Ainsworth, Pitcher & Rotinsulu, 2008;Early-Capistrán et al, 2020) to infer changes to the taxa or resources.…”
Section: How Can Conservation Happen Without Biological Monitoring Data?mentioning
confidence: 99%
“…Relative to scientific approaches, Anad on et al ( 2009) estimated that sightings of tortoises were 100 times cheaper, and Castello (2004) estimated that counts of an endangered air-breathing fish, Arapaima gigas, were 200 times cheaper and faster. Castello et al (2023) reconstructed time series of fish catch for up to 60 years in the past in three fisheries of the Congo Basin using 329 fisher interviews done by five people during 1 month of fieldwork; the research cost a tiny fraction of that for collecting conventional data on fisheries landings.…”
Section: The Advantages Of Local Knowledgementioning
confidence: 99%
“…Conducting stock assessments that rely on dataintensive methods is often impracticable in floodplaindominated tropical regions such as Amazonia (Castello et al, 2023;Shephard et al, 2020). There, fish size and abundance are heavily influenced by interannual variability in flooding as the flood pulse controls the availability of spawning, nursing, and feeding habitat, and species respond differently to hydrological stimuli and environmental pressure (Castello, Isaac, & Thapa, 2015;Welcomme, 1999).…”
Section: Introductionmentioning
confidence: 99%